Upaya Pembinaan Karakter Siswa melalui Profil Pelajar Pancasila di SMP Negeri 2 Percut Sei Tuan Tahun Pelajaran 2024/2025 - Latifah Hannum Gultom; Liber Siagian (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study aims to determine the efforts to foster student character through the implementation of the Pancasila Student Profile values ​​at SMP Negeri 2 Percut Sei Tuan in the 2024/2025 Academic Year. The main focus of the study is on the formation of discipline and cooperation characters. This study uses a qualitative approach with a descriptive method. Data collection techniques were carried out through interviews, observations, and documentation, with resource persons consisting of curriculum teachers, PPKn teachers, and grade VII students. The results of the study indicate that the implementation of the Pancasila Student Profile has been carried out through various daily habituation activities, such as Duha prayer, congregational Friday prayers, rotating class duty, nutritious Friday, clean Friday, Ramadan recitation, as well as community service and group discussions in learning. The character of student discipline is evident from the habit of being on time, carrying out responsibilities without being told, and following school rules. Meanwhile, the character of cooperation is reflected in group activities that foster an attitude of helping each other, respecting opinions, and sharing tasks. Despite obstacles such as excessive use of gadgets and minimal parental involvement, character building through daily habits has proven effective and in line with the theory of character education according to Thomas Lickona. Overall, daily habituation activities based on the values ​​of the Pancasila Student Profile can be a strategic means in shaping students' character as a whole.